EFFECT OF THIAMETHOXAM ON OXYGEN CONSUMPTION OF THE FRESHWATER BIVALVE, LAMELLIDENS MARGINALIS (LAMARCK) - MINAKSHI, RANE; A. Y. MAHAJAN, (The Bioscan, 2013)
The impact of acute and chronic dose of Thiamethoxam on the rate of oxygen consumption of the freshwater bivalve, Lamellidens marginalis was studied. After 24, 48, 72 and 96h of exposure to acute concentration, the average oxygen consumption was 0.4935, 0.4826, 0.4763 and 0.4501 (mL/gm/L/h) and after 7, 14 and 21 days of chronic exposure, it was 0.2943, 0.2925, 0.2724 (mL/gm/L/h). It was observed that the rate of oxygen consumption was decreased with increase in the exposure period. The decrease was maximum in chronic exposure as compared to acute exposure to Thiamethoxam.